2017
DOI: 10.1111/jpn.12745
|View full text |Cite
|
Sign up to set email alerts
|

Beet pulp intake and hairball faecal excretion in mixed‐breed shorthaired cats

Abstract: SummaryHairball formation may induce vomiting and intestinal obstruction in predisposed cats. Some insoluble fibres as sugarcane fibre and cellulose can prevent hairball formation. The aim of this study was to evaluate the effect of beet pulp consumption, a moderate soluble and fermentable fibre source, on faecal trichobezoars excretion in adult shorthaired cats fed kibble diets. Eighteen mixed-breed shorthaired cats and three extruded diets were used as follows: a basal diet without added fibre source (PB0-8.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 11 publications
0
17
0
Order By: Relevance
“…For example, Dann et al () reported a decrease in clinical signs (vomiting, retching and coughing) of hairballs when cats with a history of hairballs were supplemented with a 2 g gelatin capsule containing a blend of Psyllium husk and slippery elm (b.i.d) when compared to the control treatment with no added fibre. Conversely, Loureiro et al () reported no effects due to the beet pulp content (8% vs. 16%) of extruded cat foods in number of hairballs excreted on the faeces, although there was a tendency for total number of hairballs relative to mass of fresh faeces to increase. In addition, it is important to highlight that Loureiro et al () did not specify if the cats in this experiment were prone to hairballs (short‐haired cats).…”
Section: Resultsmentioning
confidence: 97%
See 4 more Smart Citations
“…For example, Dann et al () reported a decrease in clinical signs (vomiting, retching and coughing) of hairballs when cats with a history of hairballs were supplemented with a 2 g gelatin capsule containing a blend of Psyllium husk and slippery elm (b.i.d) when compared to the control treatment with no added fibre. Conversely, Loureiro et al () reported no effects due to the beet pulp content (8% vs. 16%) of extruded cat foods in number of hairballs excreted on the faeces, although there was a tendency for total number of hairballs relative to mass of fresh faeces to increase. In addition, it is important to highlight that Loureiro et al () did not specify if the cats in this experiment were prone to hairballs (short‐haired cats).…”
Section: Resultsmentioning
confidence: 97%
“…Conversely, Loureiro et al () reported no effects due to the beet pulp content (8% vs. 16%) of extruded cat foods in number of hairballs excreted on the faeces, although there was a tendency for total number of hairballs relative to mass of fresh faeces to increase. In addition, it is important to highlight that Loureiro et al () did not specify if the cats in this experiment were prone to hairballs (short‐haired cats). Finally, Armbrust et al () reported no effect of fibre content in extruded cat food on transit time; however, the authors found that round kibbles increased passage rate compared with triangular kibbles.…”
Section: Resultsmentioning
confidence: 97%
See 3 more Smart Citations